Reading popular music festivals through the lens of public sphere - Chakravarty, Devpriya (Penerbit Universiti Kebangsaan Malaysia, 2017)
The core idea of Jürgen Habermas public sphere has to do with forming a public made of private individuals who participate in civic dialogue on issues of common interest. A public so formed generates public opinion through the formation of a communicative network. This essay argues that the communicative network of the public sphere which is known to be strengthened by its cultural connects through press and mass media can also be shaped by popular music culture like hip-hop, rock or electronic dance music. A cultural public sphere is comprised of numerous networks of mass and popular culture which help in shaping the participants’ articulations of politics, both public and personal. Cultural public sphere marks the entry of affective modes of communication as effectual participation in the politics of everyday life. In this article, the author tries to position the role of popular music cultures in the formation of a public sphere by studying three distinct forms of popular music- hip-hop, rock and electronic dance music. The idea is to understand the role of the communities formed due the affective mode of popular music and the efficacies granted to these social groups in the larger context of a public sphere. Another important dimension of studying these forms of popular music is to understand music festivals as active sites for the realisation of a public sphere. Drawing from Durkheim’s idea of how festivals harness within them a ‘collective effervescence’ which he found to be an integral element to aid in instilling feelings of solidarity in a community, this essays tries to locate the popular music festival sites within the framework of a cultural public sphere by conducting an in depth literature review on how the traditional public sphere is critiqued from the vantage point of a cultural public sphere; how popular culture texts and practices inform these critiques and finally how music festival sites act as public spheres.